Young generation’s attitudes and preferences towards Malay traditional food at night markets / Muhammad Ibrahim Sa’min, Yusup Apriyanto and Muhammad Haikhal Afiqi Muhammad Edrus - Sa’min, Muhammad Ibrahim; Apriyanto, Yusup; Muhammad Edrus, Muhammad Haikhal Afiqi (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
The changing behaviour of the young generation towards Malay traditional food may pose challenges for traditional food vendors at night markets. This study investigates the purchasing behavior of the young generation towards Malay traditional food at night markets in Puncak Alam, Selangor. Employing a qualitative approach, data was gathered through observations, documentation, and spontaneous interviews. Findings reveal that food presentation, safety and cleanliness, word of mouth, taste, price, and portion size are determinants that influence the purchasing decisions of young consumers. Notably, visual appeal and hygiene practices attract customers, while peer recommendations and flavor evoke positive experiences. Reasonable pricing and generous portion sizes also play pivotal roles. Recommendations include maintaining hygiene standards, leveraging word-of-mouth marketing, preserving authentic flavors, offering reasonable prices, and providing generous portion sizes. Understanding these factors can aid vendors in sustaining and revitalizing the market for Malay traditional cuisine, ensuring its continued presence in Malaysia's lively night markets.